OPENING ADDRESS TO ARTICLE G.A. KARKASHADZE, O.I. MASLOVA, L.S. NAMAZOVA-BARANOVA «CURRENT PROBLEMS OF DIAGNOSIS AND TREATMENT OF MILD COGNITIVE IMPAIRMENTS IN CHILDREN» - article editorial (Union of pediatricians of Russia, 2011)
.